2013
DOI: 10.1186/1749-8090-8-178
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the time interval between coronary angiography and on-pump cardiac surgery on risk of postoperative acute kidney injury: a meta-analysis

Abstract: BackgroundReports of the association between the time interval from coronary angiography (CAG) to cardiac surgery and risk of postoperative acute kidney injury (AKI) are controversial. We attempted to examine this association by conducting a meta-analysis.MethodsWe searched the Pubmed, MEDLINE, EMBASE, Web of Science databases, and the Cochrane Library from January 1966 to March 2013. A meta-analysis of studies reporting data for 1-day and 3-day time intervals between CAG and cardiac surgery was conducted afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
1
15
0
1
Order By: Relevance
“…Again, results in this area are contradictory. Intravenous contrast before surgery may increase the incidence of AKI and has led to some recommendations for delaying surgery 24 to 72 hours after contrast administration; however, another study disagrees . Preoperative placement of an intra‐aortic balloon pump may prevent AKI and reduce the incidence of RRT in high‐risk patients by improving perfusion and reducing endothelial activation .…”
Section: Resultsmentioning
confidence: 99%
“…Again, results in this area are contradictory. Intravenous contrast before surgery may increase the incidence of AKI and has led to some recommendations for delaying surgery 24 to 72 hours after contrast administration; however, another study disagrees . Preoperative placement of an intra‐aortic balloon pump may prevent AKI and reduce the incidence of RRT in high‐risk patients by improving perfusion and reducing endothelial activation .…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, concerns persist in the surgical setting owing to the physiological insult of surgery potentially predisposing patients to the risk of contrast media, acting as a second hit that leads to AKI. Concerns regarding the risk of contrast‐induced nephropathy can have a significant impact on the patient care pathway, based on recommendations to undergo additional tests, withhold medications, enact protocols for periprocedural volume expansion, consider restricting use of contrast media, or potentially delay interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the association between the risk of postoperative AKI and the timing of contrast exposure before cardiac surgery have shown mixed results. Some studies have shown that the risk of AKI after CABG is inversely related to the time between cardiac angiography and CABG, including one recent meta-analysis that found that a time interval of 1 day or less between angiography and on-pump cardiac surgery was associated with increased risk of AKI (8,9). Others have reported no increased risk of AKI based on timing of contrast (10).…”
Section: Case Discussionmentioning
confidence: 99%